Unraveling the Aging Skein: Disentangling Sensory and Cognitive Predictors of Age‐related Differences in Decision Making. (9th December 2015) - Del Missier, Fabio; Hansson, Patrik; Parker, Andrew M.; Bruine de Bruin, Wändi; Nilsson, Lars‐Göran; Mäntylä, Timo
Abstract: Age‐related differences in sensory functioning, processing speed, and working memory have been identified as three significant predictors of the age‐related performance decline observed in complex cognitive tasks. Yet, the assessment of their relative predictive capacity and interrelations is still an open issue in decision making and cognitive aging research. Indeed, no previous investigation has examined the relationships of all these three predictors with decision making. In an individual‐differences study, we therefore disentangled the relative contribution of sensory functioning, processing speed, and working memory to the prediction of the age‐related decline in cognitively demanding judgment and decision‐making tasks. Structural equation modeling showed that the age‐related decline in working memory plays an important predictive role, even when controlling for sensory functioning, processing speed, and education. Implications for research on decision making and cognitive aging are discussed. Copyright © 2015 John Wiley & Sons, Ltd.